Gas Deliverability Model with Different Vertical Wells Properties - Mucharam, L.; Sukarno, P.; Siregar, S.; Syihab, Z.; Soewono, E.; Apri, M.; Irzal, F. (Journal of Engineering and Technological Sciences, 2003)
We present here a gas deliverability computational model for single reservoir with multi wells. The questions of how long the gas delivery can be sustained and how to estimate the plateau time are discussed here. In order to answer such a question, in this case, a coupling method which consists of material balance method and gas flow equation method is developed by assuming no water influx in the reservoir. Given the rate and the minimum pressure of gas at the processing plant, the gas pressure at the wellhead and at the bottom hole can be obtained. From here, the estimation of the gas deliverability can be done. In this paper we obtain a computational method which gives direct computation for pressure drop from the processing plant to the wells, taking into account different well behavior. Here AOF technique is used for obtaining gas rate in each well. Further Tian & Adewumi correlation is applied for pressure drop model along vertical and horizontal pipes and Runge-Kutta method is chosen to compute the well head and bottom hole pressures in each well which then being used to estimate the plateau times. We obtain here direct computational scheme of gas deliverability from reservoir to processing plant for single reservoir with multi-wells properties. Computational results give different profiles (i.e. gas rate, plateau and production time, etc) for each well. Further by selecting proper flow rate reduction, the flow distribution after plateau time to sustain the delivery is computed for each well.